2014
DOI: 10.3174/ajnr.a3910
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Functional MR Imaging of Peripheral Nerve Sheath Tumors: Initial Experience

Abstract: BACKGROUND AND PURPOSE Differentiating benign from malignant peripheral nerve sheath tumors can be very challenging using conventional MR imaging. Our aim was to test the hypothesis that conventional and functional MR imaging can accurately diagnose malignancy in patients with indeterminate peripheral nerve sheath tumors. MATERIALS AND METHODS This institutional review board–approved, Health Insurance Portability and Accountability Act–compliant study retrospectively reviewed 61 consecutive patients with 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
109
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 21 publications
5
109
4
Order By: Relevance
“…DCE-MRI constitutes a quantitative method for evaluating tumor profusion, for which significantly different imaging patterns have been described particularly when it comes to differentiating benign and malignant soft tissue tumors [34]. In a current article, Demehri et al observed that when DCE-MRI was used to examine 9 MPNST and 22 nerve sheath tumors, 50 % of the MPNST exhibited an early arterial contrast medium enhancement, which, however, was discovered in only 11 % of the benign peripheral nerve sheath tumors [35]. To put it simply, diffusion-weighted imaging is based on the limited diffusion (random thermal motion of water molecules) owing to the high cell density in tumors [36].…”
Section: Role Of Various Imaging Modalities For Neurofibromatosis Typmentioning
confidence: 99%
See 4 more Smart Citations
“…DCE-MRI constitutes a quantitative method for evaluating tumor profusion, for which significantly different imaging patterns have been described particularly when it comes to differentiating benign and malignant soft tissue tumors [34]. In a current article, Demehri et al observed that when DCE-MRI was used to examine 9 MPNST and 22 nerve sheath tumors, 50 % of the MPNST exhibited an early arterial contrast medium enhancement, which, however, was discovered in only 11 % of the benign peripheral nerve sheath tumors [35]. To put it simply, diffusion-weighted imaging is based on the limited diffusion (random thermal motion of water molecules) owing to the high cell density in tumors [36].…”
Section: Role Of Various Imaging Modalities For Neurofibromatosis Typmentioning
confidence: 99%
“…While a sensitivity of 100 % and a specificity of 77 % MPNST were identified at a minimum ADC value of < 1.0 × 10 −3 mm 2 /s, even this limited specificity was observed only in tumors with a diameter of ≥ 4.2 cm. An even lower specificity must be assumed for smaller lesions [35]. In another study involving 29 patients, MPNST exhibited in diffusion tensor imaging (DTI) a significantly lower diffusivity than benign tumors (0.900 ± 0.25 versus 1.848 ± 0.40 × 10 −3 mm 2 /s; p < 0.001), with this difference not being significant for ADC values from DWI sequences [37].…”
Section: Role Of Various Imaging Modalities For Neurofibromatosis Typmentioning
confidence: 99%
See 3 more Smart Citations